High nutritional quality of human induced pluripotent stem cells-generated proteins by advanced scalable peptide hydrogel 3D suspension system - Xu, Shan (Kansas State University, 2023)
Cell-cultured protein technology has become increasing attractive due to its sustainability and climate benefit. The aim of this study is to test the nutritional quality of the human induce pluripotent stem cells (hiPSCs)-cultured proteins in advanced scalable 3D peptide hydrogel system for highly efficient production of cell cultured proteins. Previous studies in Dr. Sun’s lab demonstrated an advanced PGmatrix3D (PG-3D) scaffolding hydrogel for long-term hiPSCs maintenance with significantly higher cell expansion and superior pluripotency when compared with traditional 2D cell culture or other Matrigel, Vitronectin, or Polyethylene glycol (PEG)-based 3D cell culture systems. In this study, the PGmatrix3D suspension system (PG-3DSUSP), specifically designed for scaling up cell manufacturing, was selected for 3D cultured hiPSC protein production. Results indicates that PG-3DSUSP is a competitive system to the well-established PG-3D system in terms of cell growth performance and cell pluripotency. The nutritional value of hiPSC-generated proteins including amino acid composition and in vitro protein digestibility were further evaluated. Amino acid composition of hiPSCs as measured using hydrophilic interaction chromatography liquid chromatography demonstrated a significant higher essential amino acid content (39.0%) when compared with human skeletal muscle protein (31.8%). In vitro protein digestibility of hiPSCs as measured by pH drop method showed a significant higher (78.0 ± 0.7%) when compared with commercial beef protein isolate (75.7 ± 0.6%). Taken together, this is the first study to report an advanced PG-3DSUSP culture to produce the highly efficient hiPSCs-generated proteins that possess more essential amino acids and demonstrate better digestibility. The hiPSCs-generated proteins with super nutrition quality may be of particular significance as novel alternative proteins in food engineering and industries for future food, beverage, and supplement applications.
Keywords: hiPSCs; PepGel 3D suspension culture system; Nutritional quality; Amino acid composition; In vitro protein digestibility; Regenerative agriculture